2000
DOI: 10.1177/0739456x0001900307
|View full text |Cite
|
Sign up to set email alerts
|

Does Growth Management Matter? The Effect of Growth Management on Economic Performance

Abstract: Growth management attempts to improve the ordering of development to improve outcomes. To taxpayers, growth management promises more efficient delivery of public facilities and services. To developers, growth management promises more certainty. To citizen activists, growth management promises resolution of development problems in advance, instead of on an ad hoc basis. These promises are heroic. Nonetheless, even if only partly successful, communities engaged in growth management should out-perform other commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Porter (1997) showed that land price increases in cities with growth management were largely caused by increases in attractiveness. Nelson and Peterman (2000) showed that cities with growth management on average are more successful than cities without, and Downs (2002) demonstrated that house prices in Portland have not grown faster than in other comparable metropolitan areas in the United States.…”
Section: North America: Portlandmentioning
confidence: 98%
“…Porter (1997) showed that land price increases in cities with growth management were largely caused by increases in attractiveness. Nelson and Peterman (2000) showed that cities with growth management on average are more successful than cities without, and Downs (2002) demonstrated that house prices in Portland have not grown faster than in other comparable metropolitan areas in the United States.…”
Section: North America: Portlandmentioning
confidence: 98%
“…After subsiding briefly in the early 1980s, state-level land use reforms went through a period of rapid expansion and have since been broadened to include a wide range of quality-of-life issues. Most state and regional planning programs focus on containing urban sprawl but recognize the need to accommodate growth through coordinated, wellplanned land use (DeGrove 1992;Gale 1992;Nelson et al 1995;Burby and May 1997;Porter 1997;Nelson and Peterman 2000). Although the actual degree of authority varies, federal policy (especially the Intermodal Surface Transportation Efficiency Act [ISTEA] and subsequent Transportation Equity Act [TEA21]) and renewed state interest have served to broaden the powers of regional planning organizations considerably.…”
Section: ᭤ Regulatory Growth Management In the United Statesmentioning
confidence: 99%
“…The second phase commenced with revisions to Florida's land-use laws in 1984 and1985 and continued into the early 1990s with new legislation in Delaware, Maine, Rhode Island and Vermont (DeGrove & Miness, 1992, p. 1;Gale, 1992;Burby et al, 1997, p. 2). It is distinguished from the first phase in its efforts to balance economic and environmental sustainability and equity (Nelson & Peterman, 2000;DeGrove, 2005, p. 4). In this phase, ''consistency, concurrency, compact urban forms,'' and ''quality of life issues'' took on more importance (DeGrove, 2005, p. 4).…”
Section: State-led Growth Management In the Usmentioning
confidence: 98%